Elimination of Abnormal Output Voltage in a Hybrid Active NPC Inverter - Song, Min Geun; Kim, Seok Min; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2021)
This article proposes a method to eliminate abnormal output voltages generated in three-level hybrid active neutral-point clamped (ANPC) inverters. The hybrid ANPC inverter is a topology in which silicon (Si) devices are replaced with silicon-carbide (SiC) devices in part from the conventional ANPC topology. The hybrid ANPC inverters have the advantages of high switching frequency and low power switching loss due to the SiC devices. In this hybrid ANPC inverter, abnormal output voltages occur when the polarity of the output pole voltage is changed from positive to negative. The cause of the abnormal voltages is the switching time difference between the Si and SiC devices, and it is various from a few nanoseconds to a few microseconds. These abnormal output voltages need to be eliminated as it leads to degraded output power quality in the hybrid ANPC inverters. The proposed switching method effectively eliminates the abnormal output voltages and reduces output current distortion. The performance of the proposed method is verified using a prototype of the new three-level hybrid ANPC inverter type through both simulations and experiments.
Keywords: Active neutral point clamped; High switching frequencies; Output current; Output voltages; Pole voltages; Silicon carbides (SiC); Switching methods; Switching time; Abnormal output voltage; hybrid active neutral point clamped inverters; reliability; silicon-carbide devices; three-level inverters